Dimensionamento de pessoal de enfermagem utilizando os escores TISS-28 e NEMS em uma Unidade de Terapia Intensiva Pediátrica no Sul do Brasil - Velozo, Kelly Dayane Stochero (2012)
This cohort study aimed to estimate workload and sizing of nursing staff using the Therapeutic Intervention Scoring System-28 (TISS-28) and the Nine Equivalents of Nursing Manpower Use Score (NEMS) scores in a Pediatric Intensive Care Unit (PICU). Children admitted to the PICU of a university hospital between 01/01 and 12/31/2009 were enrolled in the study. The study included 459 children with a total number of observations of 3409. Mean values for TISS-28 and NEMS were 20.8±8 and 25.2±8.7 points, respectively. Nursing workload was 14.7 hours by TISS-28 and 17.8 hours by NEMS. The estimated quantity of professionals by TISS-28 and NEMS was 39.5 and 47.7, respectively. Both scores showed good correlation and concordance. The time spent on nursing activities reflect by NEMS was significantly higher compared with TISS-28. When the sizing of nursing professionals was evaluated TISS-28 and NEMS although different, have approached reality